Taxonomic revisions of two leaf-feeding thripine genera, Chaetanaphothrips and Tusothrips (Thysanoptera, Thripidae) with descriptions of thirteen new species - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2026)
Two leaf-feeding thripine genera, Chaetanaphothrips and Tusothrips, are reviewed. The Chaetanaphothrips genus-group is redefined, and relationships between each genus among the genus-group are discussed. Eight species of Chaetanaphothrips and five species of Tusothrips are newly described: C. baliolus sp. nov., C. brevisetis sp. nov., C. coffeae sp. nov., C. linearis sp. nov., C. macrosensillae sp. nov., C. minourai sp. nov., C. okinawanus sp. nov., C. setosus sp. nov., T. baliensis sp. nov., T. fasciatus sp. nov., T. fuscipennis sp. nov., T. javanicus sp. nov., T. kenyensis sp. nov. Two illustrated keys are provided for all known species of each of these two genera. Tusothrips species are recorded from Africa, Taiwan and Japan for the first time.